Optimization Info Rate Using APSK Modulation Scheme for Delivery GSM ABIS over Satellite Communications - Hillman Damanik; Merry Anggraeni (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Mobile operators move quickly from 2G GSM networks in urban areas to remote rural areas, which are 2G networks by offering voice connectivity. As a result, more and more technology is optimizing cellular operators that reduce and perform bandwidth efficiency that will be implemented. The optimization solution for this cellular operator produces voice communication on GSM, in a cost-effective application for satellites. This paper discusses and applies to creating GSM links via satellite communication. The ABIS interface on GSM, which is defined between the Base Transceiver Station (BTS) of GSM remote cells and the Base Station Controller (BSC), is considered here to be transferred via GSM communication with the Modulation and Coding scheme 16 APSK 5/6. The MODCOD scheme determines the efficiency of what MHz is needed to send one Mbps. The efficiency value achieved by allocating, bandwidth (MHz) generated by 1.0 Mhz is an efficiency of 3.222 [bit / baud]. And Info Data Rate is generated from the value (Mbps) of 3,175. The highest traffic intensity with the value of Traffic Volume (Hours) = 3.5, Traffic Intensity (Erlang) 0.145833333. While the lowest traffic intensity with the value of Traffic Volume (Hour) = 2.6, traffic intensity = 0.108333333 (Erlang). The value obtained on Traffic Volume and Traffic Intensity is 0.1%. Service levels are very good at grade of service, because of the small possibility of access fail. Calculation of the availability of link network availability links, using ACM 16APSK LDPC 5/6 techniques that can increase up to 100%.